Outcome of central nervous system relapses in childhood acute lymphoblastic leukaemia--prospective open cohort analyses of the ALLR3 trial. - Ashish Narayan Masurekar; Catriona A Parker; Milensu Shanyinde; Anthony V Moorman; Jeremy P Hancock; Rosemary Sutton; Philip J Ancliff; Mary Morgan; Nicholas J Goulden; Chris Fraser; Peter M Hoogerbrugge; Tamas Revesz; et al. (PLoS ONE)
Unlabelled The outcomes of Central Nervous System (CNS) relapses in children with acute lymphoblastic leukaemia (ALL) treated in the ALL R3 trial, between January 2003 and March 2011 were analysed. Patients were risk stratified, to receive a matched donor allogeneic transplant or fractionated cranial irradiation with continued treatment for two years. A randomisation of Idarubicin with Mitoxantrone closed in December 2007 in favour of Mitoxantrone. The estimated 3-year progression free survival for combined and isolated CNS disease were 40.6% (25·1, 55·6) and 38.0% (26.2, 49.7) respectively. Univariate analysis showed a significantly better survival for age <10 years, progenitor-B cell disease, good-risk cytogenetics and those receiving Mitoxantrone. Adjusting for these variables (age, time to relapse, cytogenetics, treatment drug and gender) a multivariate analysis, showed a poorer outcome for those with combined CNS relapse (HR 2·64, 95% CI 1·32, 5·31, p = 0·006 for OS). ALL R3 showed an improvement in outcome for CNS relapses treated with Mitoxantrone compared to Idarubicin; a potential benefit for matched donor transplant for those with very early and early isolated-CNS relapses. Trial registration Controlled-Trials.com ISRCTN45724312.